IMPROVING STUDENTS’ SPEAKING ENGLISH PERFORMANCE BY UTILIZING YOUTUBE TED TALK VIDEOS - Faiqah, Afifah; Dollah, Syarifuddin; Amin, Fatimah Hidayahni; Adys, Himala Praptami (Universitas Negeri Makassar, 2023)
This research is to (1) determine how using TED Talks videos affects students' public speaking performances and (2) ascertain how students view TED Talks videos in the context of English classes, where they are utilized as a teaching tool for public speaking. This study employed a quantitative, quasi-experimental research strategy. First-year MA DDI Lilbanat Parepare students made up the study's population. A basic random selection group of 16 students for the experimental group and 17 students for the control group was used in the study. While the control group employed traditional teaching methods (textbook-centered method), the experimental group received therapy via YouTube TED Talk videos. Pre- and post-tests were used in this study to gather data, and a questionnaire was used to find out how students felt about the YouTube TED Talk video. The analysis of the gathered data was done with SPSS version 26. The average speaking score for the experimental group was 45 on the first exam and 53 on the second, according to the data analysis results. In contrast, the control group's average speaking score on the first and final exams was 40 and 41, respectively. In the post-test fort test, the t-value (8.345) is greater than its t-table value (2.219), and the p-values for the experimental and control groups were both less than α (0.000 < 0.05) and control groups (0.041 < 0.05). This means the null hypothesis was rejected and the alternative hypothesis accepted. This indicates that YouTube TED Talks videos affect students speaking performance. In addition, the perception of the students, obtained through the questionnaire showed that they had a positive view of the YouTube TED Talk Video.